Corporate governance mechanism for carbon emission disclosure: Evidence from state-owned enterprises in Indonesia - Andi Ina Yustina; Christine Novita Dewi; Hadi Mahmudah; Hajanirina Andreanantenaina (Global Business & Finance Review (GBFR), 2024)
Purpose: The purpose of this study is to explore how governance-related determinants affect carbon emission disclosure; if yes, whether government ownership, board diversity, and firm size mediates the relation between these determinants and carbon emission disclosure. We test ownership structure and firm-specific characteristics (board diversity, audit reputation, firm size, audit quality, leverage, and return on asset) towards carbon emission disclosure. Design/methodology/approach: Panel data analysis is used on a final sample of 120 firm-year observations of state-owned enterprises, having published sustainability reports with CED within the last 10 years (2012 - 2021). The direct and mediating effects were tested based on two econometric models and Sobel-Goodman test was conducted to check for the robustness. Findings: Results find that government ownership and board diversity can be employed as a corporate governance mechanism to facilitate public, institutional ownership and audit reputation respectively, towards improved accountability and transparency of CED. Smaller firms with lower financial performance tend to be more motivated to participate in CED in order to attract investment. Research limitations/implications: Several implications arise for various stakeholders including policymakers, and regulatory bodies interested in enhancing sustainability disclosure of firms through good CG mechanism, especially for firms with high government ownership. The findings of this research have wide implications in formulating an efficient CG mechanism for developing countries as SOEs are still prevalent. Originality/value: This study proposes the role of government ownership and board diversity as a CG mechanism and contributes to the voluntary literature, in particular, the link between CG determinants and practices underlying CED.
Keywords: 650; Corporate governance; ownership structure; firm-specific characteristics; carbon emission disclosure (CED); state-owned enterprise (SOE); Indonesia